Synthetic and Structural Studies of 4f-Metal Complexes of Oxalic Bis (Cyclohexylidenehydrazide) - Rao, T.R.; Singh, Genda (Asian Journal of Chemistry, 2010)
Oxalic bis(cyclohexylidenehydrazide) (ObCH) gave, by reaction with 4ƒ-metal chlorides, complexes of the type [Ln(ObCH)Cl2]Cl.H2O, where Ln ═ La(III), Pr(III), Nd(III), Sm(III), Eu(III), Gd(III), Tb(III), Dy(III), and Y(III). The complexes have been studied by conductance, magnetic, electronic, i.r. and 1H n.m.r. spectral techniques. I.r. and n.m.r. spectra indicate tetradentate coordination of ObCH through carbonyl oxygens and azomethine nitrogens with a polymeric linkage. Six coordination is proposed in the complexes.